THE STRATEGY FOR EDUCATION POLICY IN BORDER AREA IN THE POST-COVID-19 PANDEMIC DIGITAL ERA A Study Using a Human Security Approach in the Policy Management of the Indonesia-Malaysia border area in Nunukan Regency, North Kalimantan Province - Harsen Roy Tampomuri; Yuni Murni Tampomuri; Margaretha Hanita (Jurnal Communitarian (Prodi Ilmu Politik), 2023)
AbstractThe Human Development Index (HDI) has three primary indicators: health, education level, and economy. Education is one of the vital indicators in the HDI, and it is highly relevant to the context of developing the country's border areas. The border areas in Indonesia are still vulnerable to disparities in facilities and quality of education. Nunukan Regency, as a border area between Indonesia and Malaysia, has various dynamics and policy needs to improve the education sector. This paper elaborated on the adaption and alternative education policy in Nunukan Regency as an area with border characteristics in the post-Covid-19 pandemic digital era. The theories used in this paper are related to border management policy, the Theory of Boundary Making from Jones S. B and Human Security from Roland Paris, and the concept of digitalization from Yoo and Lyytinen. A qualitative method was used, with the research results were expected to provide solutions for policy strategies in the educational management at the borders.Keywords: Digital, Human Security, Education, Border